PENGEMBANGAN SUMBER DAYA MANUSIA UNTUK MENINGKATKAN KUALITAS PENDIDIKAN (STUDI KASUS PADA SMA) - Siti Alifah (Journal on Teacher Education, 2021)
Abstract Incrcteasing human resources in the era of globalization was very important to improve the quality of education. However, there are still some obstacles and problems that need to be addressed. From the lack of teachers, in various remote areas, the quality of teachers, facilities and infrastructure are still minimal. This study aimed to describe the development of human resources in several high schools in Bekasi City. The research method used is descriptive qualitative research method. Data were obtained by interviewing and giving questionnaires. Data analysis techniques with data collection with data reduction and data categorization. Respondents included 5 teachers, 3 principals and 5 administrative staff from 3 high schools. The results showed that the teacher's competence was on average good. This can be an illustration, so that teacher competence can be improved, although based on interviews, teachers still have big challenges in improving the quality of education. Keywords: human resource, Quality, Education